Social Injustice in Colombian Labor for the Radioactive Effects of Radon Gas During Mining Exploration and Exploitation - M, Moreno, Manuel; Giacomo, Lavezzari; Raquel, Moreno; S, Neira, Jhon; Edison J, Vásquez; Nathaly, Reyes (Journal of Posthumanism, 2025)
This article delineates the State’s omission, which should prioritize the general welfare and enhancement of the quality of life of all residents in Colombian territory, particularly in the context of workers in the mining sector, where these individuals, due to historical, social, and labor factors, find themselves in a state of marginalization social and legal. These workers are particularly vulnerable to the risk factors associated with radioactive exposure to radon gas (Rn 222) and its descendants, such as polonium 218 and 214 (Po) and lead 214 (Pb). It is crucial to acknowledge the studies conducted over the past five decades, which have elucidated the damages effects of radon gas in the mining sector. In Colombia, there is a paucity of research and studies focusing on this noble gas, as well as on the development of effective strategies for the monitoring and protection of workers in the context of the mining sector, where workers are exposed to significant risks associated with radioactive substances. The main objective of the article is to evaluate the radioactive effects of radon gas in the Colombian mining sector and the minimum guidelines for safety and health at work.